Divine Brews and Spiritual Insights: Exploring Islamic Preaching through Coffee Culture in Aceh - Aqila, Fairuza; Kurniawan, Rahmat (Insaniyat: Journal of Islam and Humanities, 2024)
Islamic preaching, or dawah, has gained attention for effectively conveying religious messages to modern society. One interesting phenomenon is using coffee shops as a space for dawah. These places have become inclusive spaces that invite participation from various social segments due to their relaxed and friendly atmosphere. This research aims to explore the role of coffee shops in facilitating society's spiritual growth and to understand the factors that attract people to participate in dawah activities in these places. The methodology used a qualitative approach that incorporated in-depth interviews and participatory observations. The findings suggest that dawah in coffee shops is effective due to the relaxed and amicable ambiance, opportunities for discourse on religious matters, engaging dawah strategies, and inclusive accessibility. Using everyday narratives and analogies in the dawah approach makes religious messages more understandable and memorable to the public. This research concludes that coffee shops can enhance spiritual growth in society by promoting Islamic teachings through coffee culture. It highlights the vital role of coffee shops in facilitating spiritual growth and improving the effectiveness of dawah activities.